The Effect of Tacrine on Functional Response of the Lower Oesophageal Sphincter Assessed by Endoscopic Luminal Impedance Planimetry in Experimental Pigs - Bures, Jan; Novak, Martin; Radochova, Vera; Kohoutova, Darina; Prchal, Lukas; Martinek, Jan; Mares, Jan; Cerny, Jaroslav; Suchanek, Stepan; Pejchal, Jaroslav; Voxova, Barbora; Urbanek, Petr; et al. (Pharmaceuticals (Basel, Switzerland), 2024)
Background/Objectives: Tacrine is a centrally active non-competitive reversible acetylcholinesterase inhibitor. It also exerts antagonising activity against N-methyl-D-aspartate receptors. Tacrine was approved for the treatment of Alzheimer's disease in 1993, but was withdrawn from clinical use in 2013 because of its hepatotoxicity and gastrointestinal side effects. Nevertheless, tacrine is currently facing a renewed wave of interest primarily due to several new tacrine-incorporated hybrids and derivates. There were two specific aims for this study: firstly, to explain the mechanisms of the adverse action of tacrine, as a distinctive example of a highly effective acetylcholinesterase inhibitor; and secondly to check whether luminal impedance planimetry is feasible for preclinical testing of possible side effects of compounds potentially toxic to the gastrointestinal tract. Methods: Six experimental pigs were used as the animal model in this study. Five major parameters were evaluated: luminal pressure (mmHg), estimated diameter (mm), cross-sectional area (mm2), distensibility (mm2/mmHg), and zone compliance (mm3/mmHg). All measurements were performed before and 360 min after intragastric administration of 200 mg tacrine (at the porcine tacrine Tmax). Results: This study consistently demonstrated an increase in luminal pressure (a directly measured indicator) for the particular balloon filling volumes used, and inversely a reciprocal decrease in the other parameters after tacrine administration. Conclusions: Endoscopic luminal impedance planimetry is a feasible method to evaluate functional response of the lower oesophageal sphincter to tacrine in experimental pigs. Tacrine did not compromise the function of the lower oesophageal sphincter either toward oesophageal spasms or, in contrast, decreased competence of the lower oesophageal sphincter.
Keywords: lower oesophageal sphincter; experimental pigs; endoscopic luminal impedance planimetry; Alzheimer’s disease; tacrine